Science Literacy Analysis in Students of SMPN 40 Makassar through the Implementation of STEM-Based E-Modules - Rifda Nur Hikmahwati Arif; Fitrah Sukmadewi M; Dr. Nurhayani H. Muhiddin (ARRUS Journal of Social Sciences and Humanities, 2025)
This study aims to analyze the ability of science literacy in the knowledge aspect of junior high school students. The type of research used is survey research method. The research design used was descriptive survey. This research was conducted in January-February even semester of the 2025/2026 academic year at SMPN 40 Makassar. The population in this study were all students of class IX UPT SPF SMP Negeri 40 Makassar in the 2024/2025 school year consisting of 5 classes with a total of 190 students. Sampling was done by random sampling technique. The sample used was 1 class, namely class IX.5 with a total of 35 students. The data collection technique was carried out by giving a test on the knowledge aspect of science literacy in the form of a multiple choice test totaling 20 numbers. The results of the analysis show that the science literacy of junior high school students is still at a moderate level, with an average score of 10.11 out of a maximum total score of 20 and a standard deviation of 2.21, which reflects a moderate variation in ability. A total of 62.86% of students were in the moderate category, 22.86% in the high category, and 14.29% in the low category. The distribution of scores for each indicator showed that in the content aspect (A.01), 54% of students reached the correct answer, in the procedural aspect (A.02) only 42% of students answered correctly, while in the epistemic aspect (A.03) there were 51% of students who answered correctly.